1993
DOI: 10.1002/gps.930080606
|View full text |Cite
|
Sign up to set email alerts
|

Clock‐drawing and dementia in the community: A longitudinal study

Abstract: SUMMARYThe clock-drawing test was used in a longitudinal study of 183 dementing individuals and their caregivers. Clockdrawing performance was measured by a simple standardized score which correlated significantly with other measures of cognitive function. Clock performance showed high individual consistency of performance as well as a significant deterioration from the initial level of performance to that obtained at 1-year follow-up. Dementing individuals who had experienced a significantly greater decline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
398
2
49

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 482 publications
(462 citation statements)
references
References 9 publications
(11 reference statements)
8
398
2
49
Order By: Relevance
“…A clock drawing task is part of this instrument and uses the following instruction: "Draw the face of a large clock, place all the numbers inside and place the pointers indicating 11:10 (eleven hours and ten minutes)". The clock drawing of each patient -copied and identified with its respective register number -was analyzed retrospectively by five researchers who had no access to the patient's file and were unaware of the cognitive condition of the subjects; each researcher applied one of the following four methods: Manos, 11 Shulman et al, 12 Wolf-Klein et al 13 and Sunderland et al 14 proposals. The fifth researcher applied the Manos method, 11 and thus this test was assessed by two researchers with the aim of evaluating its inter-rater reliability.…”
Section: Clock Drawing Test and Study Tests And Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…A clock drawing task is part of this instrument and uses the following instruction: "Draw the face of a large clock, place all the numbers inside and place the pointers indicating 11:10 (eleven hours and ten minutes)". The clock drawing of each patient -copied and identified with its respective register number -was analyzed retrospectively by five researchers who had no access to the patient's file and were unaware of the cognitive condition of the subjects; each researcher applied one of the following four methods: Manos, 11 Shulman et al, 12 Wolf-Klein et al 13 and Sunderland et al 14 proposals. The fifth researcher applied the Manos method, 11 and thus this test was assessed by two researchers with the aim of evaluating its inter-rater reliability.…”
Section: Clock Drawing Test and Study Tests And Proceduresmentioning
confidence: 99%
“…The researchers standardized these different methods by three procedures: 1) reading of the original texts with the description of the items and subsequent studies that used them; 2) intense discussion about the operational aspects to establish standardization in the instrument's application; 3) a pilot project with 35 clock drawings which confirmed that the standardization of these four methods among the members of the research team was excellent. The intraclass correlation coefficient (ICC) results were: 0.96 (95% CI 0.88-0.98); 0.95 (95% CI 0.90-0.98); 0.89 (95% CI 0.79-0.95); 0.97 (95% CI 0.95-0.99) for the Manos, 11 Shulman et al, 12 Wolf-Klein et al, 13 and Sunderland et al…”
Section: Clock Drawing Test and Study Tests And Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these scoring systems have also been tailored specifically to detect impairment related to specific disorders (Mendez et al, 1992;Rouleau et al, 1992). Some scoring systems follow a set of clear quantitative guidelines that outline certain components of the CDT that should be scored individually (i.e., number placement and number spacing) (Mendez et al, 1992), while some follow a more abstract qualitative guideline for scoring (i.e., minor visuospatial errors and severe level of disorganization) (Shulman et al, 1993). Despite the variability in scoring systems, it has been shown that simpler scoring systems are often better (Mainland and Shulman, 2013).…”
Section: Introductionmentioning
confidence: 99%